Pelaksanaan Perjanjian Pemberian Pinjaman Khusus Antara Bank Ntb Syariah Dengan Anggota Ikatan Pengusaha Muslimah Indonesia (IPEMI) - Mita Lestari; Rahmawati Kusuma (Private Law, 2022)
This research aims are to know how the implementation of provision specific loans between Bank NTB Sharia with UMKM IPEMI member and how is the default settlement mechanism will be taken by Bank NTB Sharia if another party breach the contract. This research is qualified as normative empirical legal research. the research result shows that Bank NTB Sharia provide convenience for the UMK in the loan process until it realization with bigger opportunity, because of UMKM IPEMI is an association which have big success rate and also contribute in regional economy empowerment. The dispute settlement mechanism is conducted by the Bank NTB Sharia according to Article 55 Law Number 21 of 2008 and Article 26 of Murabahah Loans Contract of Bank NTB Sharia.